2021
DOI: 10.1186/s12936-021-03604-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the durability and use of long‐lasting insecticidal nets in Nicaragua

Abstract: Background Vector control for malaria prevention relies most often on the use of insecticide-treated bed net (ITNs) and indoor residual spraying. Little is known about the longevity of long-lasting insecticidal nets (LLINs) in the Americas. The physical integrity and insecticide retention of LLINs over time were monitored after a bed net distribution campaign to assess community practices around LLIN care and use in Waspam, northeastern Nicaragua. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Intriguingly, despite predelivery inspection reports indicating adequate total AI content, the bioefficacy of these LLINs in standardized WHO cone bioassays was low and highly variable with an average 24h mortality of just 39.4% for new nets that had never been used or washed 7 . A study from Nicaragua, published in early 2021, showed similar deficiencies for the same LLIN product, with strikingly low mortality rates for pyrethroid susceptible mosquitoes (less than 20%) just 6 months after distribution 8 . These findings stand in stark contrast to the bioefficacy of Permanet 2.0 ® manufactured prior to 2013, which was consistently 100% in cone bioassays, even after extended periods of usage 9 .…”
Section: Introductionmentioning
confidence: 85%
“…Intriguingly, despite predelivery inspection reports indicating adequate total AI content, the bioefficacy of these LLINs in standardized WHO cone bioassays was low and highly variable with an average 24h mortality of just 39.4% for new nets that had never been used or washed 7 . A study from Nicaragua, published in early 2021, showed similar deficiencies for the same LLIN product, with strikingly low mortality rates for pyrethroid susceptible mosquitoes (less than 20%) just 6 months after distribution 8 . These findings stand in stark contrast to the bioefficacy of Permanet 2.0 ® manufactured prior to 2013, which was consistently 100% in cone bioassays, even after extended periods of usage 9 .…”
Section: Introductionmentioning
confidence: 85%
“…Thorough characterization of resistant strains before each evaluation, or close to the time of an evaluation is recommended since even standard strains vary in their phenotypic expression of resistance through time [ 43 ]. The use of resistant strains for evaluation of regeneration time of pyrethroid only nets may give supplementary information on true regeneration time, although the use of the median time to knock down [ 37 ] or median time to take off [ 30 ] may give a more sensitive measure of surface concentration using susceptible test systems. New videography methods that quantify mosquito interaction with the net surface show great promise in standardization of these measurements [ 44 ].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…A method has been developed using net titration before and after washes in soap water or insolvents, that is designed to measure the time it takes for the surface concentration of one or more insecticides to become stable, i.e., the regeneration time (Skovmand, pers.commun.). Surface concentration of permethrin-treated nets has been assessed by rubbing the surface of an ITN with a cotton sample using a Martindale machine (normally used to determine the abrasion and pilling resistance of all kinds of textiles) and analysing the chemical on the cotton sample by HPLC, which correlated with bio efficacy via median time to knock down [ 37 ]. Greater uptake of existing methods is needed to generate the data required for recommendation of such tests as a regular part of product testing.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: Bioefficacy, Bioassay, Cone bioassay, Tunnel test, Insecticide treated nets, ITN, Long lasting insecticidal nets, LLIN, Pyrethroid, Mosquito, Anopheles, Malaria, Quality assurance chemical tests such as high performance liquid chromatography and gas chromatography with mass spectrometry have not yet been found to correspond well to bioefficacy results [34].…”
Section: Introductionmentioning
confidence: 99%